Development of bioconjugate from streptomyces tyrosinase and gold nanoparticles for rapid detection of phenol constituents - Zainab, Mazhari Bi Bi; Madhusudhan, D. N.; Raghavendra, H.; Dastager, Syed Gulam; Dayanand, Agsar (Indian Journal of Experimental Biology, 2014)
Most of the phenol compounds are toxic and have been considered as hazardous pollutants. Several physicochemical and biological methods are available to detect and monitor the phenol pollutants in water and soil. In the present study, phenol constituents of winery, paper and plastic industrial effluents were successfully detected employing tyrosinase-gold nanoparticles bioconjugate. The synthesis of extracellular tyrosinase and gold nanoparticles was achieved by a single isolate of Streptomyces sp. DBZ-39. Enhanced production (369.41 IU) of tyrosinase was produced in submerged bioprocess employing response surface method with central composite design. Extracellular gold nanoparticles synthesized (12-18 nm) by Streptomyces sp. DBZ-39 were characterized with TEM, EDAX and FTIR analysis. A rapid detection (within 10 min) of phenol constituents from winery effluents was achieved by bioconjugate, when compared to tyrosinases and gold nanoparticles independently. Streptomyces tyrosinase could exhibit relatively a better performance than commercially available mushroom tyrosinase in the detection of phenol constituents. Winery effluent has shown much higher content (0.98 O.D) of phenol constituents than paper and plastic effluents based on the intensity of color and U.V absorption spectra.
Keywords: Bioconjugate; gold nanoparticles; Phenol detection; Streptomyces; Tyrosinase